Mutagenicity of PM10-bound PAHs from non-exhaust sources - Vicente, Estela Domingos (2022)
Road trafc is a major source of airborne particles. While exhaust emissions have been deeply scrutinised, non-exhaust emissions deserved less attention despite their rising contribution to particle emissions from trafc. The mutagenicity of particulate matter (PM10) samples from wear between pavements and tyres and from road dust resuspension was determined by the Ames test with two Salmonella typhimurium strains (TA98 and TA100) with or without metabolic activation. After sequential extraction of PM10 samples in dichloromethane and methanol, the extracts were separated via fash chromatography and the subfraction that contained polycyclic aromatic compounds (PAHs) was used in the assays. Additionally, the samples were analysed by gas chromatography-mass spectrometry (GC–MS). The analysed extracts contained predominantly high molecular weight PAHs with varying concentrations. The non-exhaust trafc-related source samples did not reveal mutagenic potential at the doses examined. Given the compositional complexity of the samples, aggregating multiple metals and organic compounds of diferent polarities, an integrated assessment of the toxicity of non-exhaust particles should include other in vitro toxicity assays.